Mouse models of peripheral metabolic disease. Issue 3 (June 2018) - da Silva Xavier, Gabriela; Hodson, David J.
Abstract : Metabolic disease risk is driven by defects in the function of cells that regulate energy homeostasis, as well as altered communication between the different tissues or organs that these cells occupy. Thus, it is desirable to use model organisms to understand the contribution of different cells, tissues and organs to metabolism. Mice are widely used for metabolic research, since well-characterised mouse strains (in terms of their genotype and phenotype) allow comparative studies and human disease modelling. Such research involves strains containing spontaneous mutations that lead to obesity and diabetes, surgically- and chemically-induced models, those that are secondary to caloric excess, genetic mutants created by transgenesis and gene knockout technologies, and peripheral models generated by Cre-Lox or CRISPR/Cas9 approaches. Focussing on obesity and type 2 diabetes as relevant metabolic diseases, we systematically review each of these models, discussing their use, limitations, and future potential.